Detection of cortical lesions in multiple sclerosis: A new imaging approach. (15th September 2015) - Patel, Kevin R; Luo, Jie; Alvarez, Enrique; Piccio, Laura; Schmidt, Robert E; Yablonskiy, Dmitriy A; Cross, Anne H
Cortical lesions occur early in multiple sclerosis (MS) and are thought to have clinical implications. Conventional MRI is insensitive to cortical pathology. Investigational imaging modalities show improved but incomplete cortical lesion detection and are time and resource intensive. Gradient echo plural contrast imaging (GEPCI) is sensitive to MS white matter pathology and can be performed on standard MRI scanners. Here we used GEPCI to examine autopsied MS frontal brain tissues. Two cortical MS lesions were visually distinguished from surrounding tissue by GEPCI and immunohistochemical staining. Furthermore, these lesions were quantitatively differentiated from healthy tissue using GEPCI-derived metrics.